PENGEMBANGAN MEDIA MISTERY BOX PADA MATA PELAJARAN IPAS MATERI SISTEM PENCERNAAN UNTUK MENDUKUNG MINAT BELAJAR SISWA KELAS V SEKOLAH DASAR - Kodiriyah, Ain Nun Sila; Sutrisno AB, Joko; Rahmawati, Endah (Jurnal Muassis Pendidikan Dasar, 2025)
This development research is motivated by the problem of less varied learning and low interest in learning among students. Teachers only use textbooks due to the lack of availability of learning media. This study aims to develop mystery box media, determine the feasibility of the media and the effectiveness of the media to support student interest. This research and development uses the ADDIE model with five stages, namely analysis, design, development, implementation and evaluation. Data collection techniques in this study are observation, interviews, and questionnaires. Based on the results of the validation of experts, the values obtained were material experts of 86.15% with the criteria of "very feasible", media experts of 96.6% with the criteria of "very feasible" and language experts of 88% with the criteria of "very feasible". Small group tests produced an average value of 100% with the criteria of "very high". Field trials obtained an average value of 98.42% with the criteria of "very high". Thus it can be concluded that the development of mystery box media greatly supports student interest in learning and is feasible to use in the learning process.